Progress for Young Mainers Paved by Education - Delorge, Michael (Maine Policy Review, 2020)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2020 asked students to propose how they would make Maine “the way life should be” for young people so that more of them will choose to live in a state with one of the oldest populations in the nation. Essays have been edited for length. This is the second-place essay.
Keywords: demographics; aging population; youth out-migration; education